Effectiveness and safety of apixaban vs warfarin among older venous thromboembolism patients stratified by race. (14th October 2021) - Cohen, A; Sah, J; Dhamane, A; Lee, T; Rosenblatt, L; Hlavacek, P; Emir, B; Keshishian, A; Yuce, H; Luo, X
Abstract: Background: Race has been identified as a risk factor for venous thromboembolism (VTE), with Black individuals having a higher risk of VTE compared to Caucasians. Black patients have been underrepresented in clinical trials evaluating anticoagulants for VTE. There has been limited evidence about the effects of anticoagulants for Black patients with VTE in routine clinical practice. Purpose: To evaluate the risk of recurrent VTE, major bleeding (MB), and clinically relevant non-major (CRNM) bleeding among VTE patients initiating apixaban or warfarin stratified by race. Methods: Older VTE patients (≥65 years) who initiated apixaban or warfarin were selected from the CMS Medicare database (September 2014–December 2017). Stabilized inverse probability treatment weighting (IPTW) was used to balance the differences between apixaban and warfarin cohorts. After IPTW, subgroup interaction analysis was conducted to evaluate if treatment effects were different between Black and White patients in the Medicare population. Due to small sample size, other races were not included in the interaction analysis. Cox proportional hazard models were used to evaluate if there was significant interaction (p<0.10) between treatment and race on recurrent VTE, MB, or CRNM bleeding. Results: A total of 22, 135 apixaban and 45, 840 warfarin patients with VTE were included in the analysis. Post-IPTW, patient characteristics were balanced between apixaban and warfarin treatment cohorts. Apixaban patients had significantly lower risk of recurrent VTE, MB, and CRNM bleeding compared to warfarin patients (Figure). When stratified by race, 57, 008 (83.9%) were White, 7, 832 (11.5%) Black, and 3, 135 (4.6%) other races. For both treatment cohorts, age was similar between Black (77.0–77.2 years) and White (77.4–77.5 years) patients. However, Black patients were more likely to have an inpatient VTE event (77.3–77.8% vs. 63.1–63.3%), a provoked VTE event (78.6–79.5% vs 69.4–69.6%), and a higher comorbidity index score (mean 4.1 vs. 2.7) compared to White patients with VTE. The incidence rates per 100 person-years of recurrent VTE (2.0–3.3 vs 1.4–2.2) and MB (7.4–10.1 vs 3.5–5.3) were also numerically higher for Black patients compared to White patients. Across both race groups, apixaban patients had a lower incidence rate of recurrent VTE, MB and CRNM bleeding compared to warfarin patients. No significant interaction was observed between treatment and race for recurrent VTE, MB, or CRNM bleeding (Figure). The findings within each race group were consistent with those of the overall VTE population. Conclusion: Among older VTE patients, disparities were observed in VTE characteristics and clinical outcomes between Black and White patients. Across both race groups, apixaban had lower risk of recurrent VTE, MB, and CRNM bleeding compared to warfarin patients. Further studies are needed to identify optimal management strategies for Black patients with VTE. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer IncBristol-Myers Squibb Company